E-textbooks and new technologies. Opportunities and openings for a reflective teacher = E-podręcznik i nowe technologie. Możliwości i otwarcia dla refleksyjnego nauczyciela - Kopaczyńska, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The world of new technologies and changes observed in the functioning of contemporary children open new possibilities for early school education teachers. This, however, requires a shift in emphasis from teachers` activity to children?s activity, initiation of work strategies based on cooperation among pupils, inclusion of discussion and other communication forms, exchange of ideas among education participants. This is to be achieved by means of new technologies, for example, e-learning or e-textbooks, which are a natural consequence of the dynamic development of modern information technologies.
Keywords: new technologies; flipped classroom; e-textbooks; reflexivity; constructivism; nowe technologie; odwrócona klasa; e-podręcznik; refleksyjność